Antibiotic resistance of Vibrio cholerae isolated from environmental water and clinical samples - Elexson, Nillian; EASTERINA EMPINA, EDWIN; Mastura, Sani; Sharifah N., W.A; Manju, S.; Bryan, V.L.Q.; Clement, E.; Vaneesa, T.; Aazhaiqal, A. R.; Rinai, K. R.; T. Y., Thung; Patricia, G. (Rynnye Lyan Resources, 2025)
Vibrio species are classified as potential hazards because of their tendency to impart serious diseases that can cause death if not well treated. The symptoms associated with a Vibrio spp. infection are usually gastrointestinal, commonly expressed as watery diarrhea, abdominal cramping, nausea, vomiting, and fever. Vibrio cholerae is a foodborne bacterial pathogen that may cause infections in humans through the ingestions of food and water contaminated with this microorganism. The emergence of antimicrobial and multidrug-resistant bacteria is another serious global health concern. Antibiotics are commonly used to treat infections in humans,animals, and in aquaculture to prevent bacterial diseases. In this study, the antibiotic susceptibility test of V. cholerae in environmental water and clinical samples were determined. V. cholerae were isolated from environmental water samples (n = 3), moore swab (n = 6), stool (n = 2) and rectal swab (n = 15). The isolation and confirmation of the presumptive of Vibrio cholerae was performed by using 2 types of selective agar, Thiosulfate Citrate bile salts sucrose agar and CHROMAgar Vibrio, and were identified using the API 20E microtest. Antimicrobial resistance profiles were determined using a disk diffusion assay against 22 antibiotics. The Vibrio cholerae isolates showed high to moderate resistance (2 or more antibiotics) to ampicillin, amoxycillin, bacitracin, cephalothin, gentamicin, imipenem, kanamycin, meropenem, penicillin, rifampin, spectinomycin, streptomycin, but were susceptible to ciprofloxacin, nalidixic acid, chloramphenicol, erythromycin, tetracycline, ceftazidime, amoxycillin, norfloxacin, enrofloxacin, imipenem, amikacin and norfloxacin. Interestingly, all (100%) of the isolates were resistant to bacitracin and penicillin, while multiple antibiotic resistance (MAR) index ranged from 0.09 to 0.27. Only 2 isolates have high reading of MAR index exceeding 0.2. Hence, considering the possible changing patterns in consumption of certain antibiotics in clinical and agricultural settings and the implementation of new antibiotics, it is necessary to determine the antibiotic resistance pattern of V. cholera and to employ the most effective antibiotic treatment.